Coordination, Communication, and Information: How Network Structure and Knowledge Affect Group Behavior. Issue 1 (2nd April 2020) - McCubbins, Mathew D.; Weller, Nicholas
Abstract: Communication is central to solving coordination problems in politics. In this paper, we show that both the communication network and what people know about the network structure affect coordination. Increases in the number of connections between people make coordination easier and so does increasing the amount of information people have about the structure. We also demonstrate that highly connected nodes in the network can facilitate coordination, but only if individuals have sufficient knowledge to identify the presence of these nodes. Our results suggest the importance of understanding network knowledge and its effects on behavior.